Characterization and antioxidant activity of peel extracts from three varieties of citrus sinensis - Ogo Ogo; Ngutor Hembafan; Raphael Amokaha; Oloche Jeremiah; Bawa Inalegwu (Heliyon, 2024)
High volume of postharvest materials including peels from citrus fruits is periodically generated, which contributes to environmental pollution. Investigating the chemical composition cum antioxidant property of these ‘wastes’ would be instructive in achieving value addition in the food and pharmaceutical value chain. On this premise, this study carried out phytochemical screening and antioxidant activity of three (3) commonly cultivated citrus varieties namely Citrus sinensis ‘valencia’, Citrus sinensis ‘washinton’ and Citrus sinensis ‘thompson navel’. The peels were extracted using ethanol and hexane in a Soxhlet extractor and thereafter subjected to phytochemical and Gas Chromatography/Mass Spectrometry (GC/MS) analyses, ferric ion reducing antioxidant power (FRAP), hydrogen peroxide scavenging and cupric ion reducing antioxidant capacity (CUPRAC) assays to evaluate their antioxidant potentials. Results show that Citrus sinensis peel extracts contain alkaloids, flavonoids, phenols, phytosterols, diterpenes, tannins and glycosides. GC/MS analysis identified about 48 compounds in each extract; with the predominant bioactive compounds being limonene (16.5%), ascorbic acid (17.7%), stearic acid (26.3%), linalool (4.7%), linoleic acid (16.18%), palmitic acid (15.23%), pentadecyclic acid (1.1%). Ethanol and hexane extracts of Valencia exhibited higher FRAP (9.09 ± 0.13) and CUPRAC (2.04 ± 0.06) values while the ethanol extract of Ibadan sweet demonstrated greater hydrogen peroxide scavenging activity (1.39 ± 0.00). Citrus peels are rich in bioactive compounds with excellent antioxidant activity and may serve as potential sources of natural antioxidants for food products or pharmaceutical formulations.